EFEKTIVITAS PELATIHAN SMART MOSLEM UNTUK MENINGKATKAN SELF CONCEPT REMAJA - widya laksana, budiarda; Wulandari, Eka Safitri (AflahConsilia : Jurnal Bimbingan dan Konseling, 2023)
MA Al-Hijrah Ngawi students all live in boarding schools and there are many religious activities in it. So that students carry out activities according to what has been scheduled by the boarding school, but there are still some students who are not fully able to manage time, realize the importance of actively participating in all activities, and these indicators show that there are still some students with low self-concept. This study aims to improve the condition of self-concept in grade XI adolescents at MA Al-Hijrah Ngawi through Smart Moslem training. The type of research used is quantitative with experimental research type Design Pre-one group pretest-posttest without control group. The subjects of this study were 11th grade students. The data collection methods are observation, short interview, scale and documentation. The analysis method is statistical data. The results of this study are, the implementation of Smart Moslem training can improve the self-concept of adolescent students at MA Al-Hijrah Ngawi, it is found that the pre-test results state the condition of low adolescent self-concept. Thus, Smart Moslem training helps adolescents in improving adolescents' self-concept, as evidenced by the increased post-test results, Smart Moslem training is carried out through several stages, including: the introduction stage, the elaboration stage, the activity implementation stage and the termination stage, The influence of Smart Moslem training that is carried out results in several positive behaviors including having clear, planned life goals, having strong self-awareness, being able to manage time well and increase activeness in all activities. Such is the influence produced by Smart Moslem training. The results of Smart Moslem training state that it is effective and has increased, it can be seen by an increase in knowledge and understanding of self-concept seen from the results of the pre-test 73.11 and post-test 96.88 with a percentage result of 31.30%, so it can be said that treatment in the form of Smart Moslem training is successful and effective to be used to improve self-concept (self-concept) in adolescents in class XI MA Al-Hijrah Ngawi.